Cytidine does not affect acute toxicity of intravenously administered choline - Synoradzki, Kamil; Swiatkiewicz, Maciej; Grieb, Paweł (Folia Neuropathologica, 2024)
Cytidine-5’-diphosphocholine (CDP-choline) is a key precursor for the intracellular synthesis of phosphatidylcholine and other phospholipids. Following either intravenous or oral application citicoline (CDP-choline of exogenous origin) undergoes quick decomposition to cytidine and choline, and for this reason it is frequently considered a prodrug. However, upon acute intravenous application in mice citicoline is, on a molar basis, 20 times less toxic than choline. To find out whether cytidine may attenuate toxicity of choline, in the present experiments we compared maximum tolerated doses of single intravenous injections of choline and equimolar mixture of choline and cytidine. We assumed that, if after oral intake a substantial part of citicoline is catabolised already in the intestine and its catabolites enter blood separately, intravenously applied equimolar mixture of cytidine and choline will be markedly less toxic than an equivalent molar dose of choline. However, the maximum tolerated single doses determined in our experiment for choline and equimolar mixture of choline and cytidine were similar. These data suggest that citicoline taken orally is not significantly decomposed in the intestinal lumen, but absorbed to blood as the intact molecule.